OBSERVASI EFEK EKSTRAK ETANOL DAUN BAMBU JAWA (Gigantochloa atter (Hassk.) Kurz) DENGAN PARAMETER FISIK DAN FISIOLOGI HEWAN UJI TIKUS (Rattus sp.)YANG DIINDUKSI BORAKS - Airlangga, Hardadi; Safitri, Endand; Arfarita, Novi (El-Hayah : Jurnal Biologi, 2015)
Bamboo Jawa leaves (Gigantochloa atter) is known to contain antioxidant compound sandhas been used as abeverage from generation to generation invarious Asiancountries. While in Indonesia, currently borax widely abusedas a food preservative and food additives. Borax produce exogenous free radicals that can lead to organ damage due to oxidative stress.This current study was to observe the effect of ethanolic extract of G. atter leaf using physiology and physical parameter onthe levels of SOD, MDA and the hepatosite necrosis totalof rats induced by borax. Borax will generate free radicals which cause cell damage through lipid peroxidation there by increasing the levels of MDA and lower SOD antioxidant. Borax metabolism occurs mostlyin theliver, therefore, one of the organs damaged by borax is liver The method of this research was experimental control group posttest only using wistar rats which divided into five groups. The negative control group was induced by aquades. The positive control group was induced by borax 1gr/kg BW and treatment group was induced by borax. Ethanolic extract of G. atter leaf was given with doses of 10mg/ml, 20mg/ml and 40mg/ml for 21 days. After 21 days of treatment, hepatocite necrosis was then observed and counted using microscope trinocular 1000x. SOD examination was conducted by the NBT test while the MDA using TBA test. Data analysis was using one way ANOVA test. G. atter ethanolic extract dosageof 10 mg/ml, 20 mg/ml and 40 mg/mlcould decrease the number of liver cells necrosis. They were 23%, 39% and 63% respectivelly when compared to positive control. Extract ethanolik of G.Atter leaf also could improve SOD and decrease MDA rats serum which induced by borax. The effective dose is 20mg/ml.